Respuesta :

Hello!


Let's solve it step by step: Find the value of "a"

[tex]5(a - 1) - 9(a - 2) = - 3(2a + 1) - 2[/tex]

Solving:
1º Pass: Delete the parentheses, effecting the distributive property, multiply the number of outside the parentheses with the ones inside, not forgetting to make the signal game.

[tex]5a - 5 - 9a + 18 = - 6a - 3 - 2[/tex]

2º Pass: Put the numbers with letter to the left of the equality and the numbers without letter to the right of the equality, remembering that, changes the signal when changing sides.

[tex]5a - 9a + 6a = - 3 - 2 + 5 - 18[/tex]

3º Pass: Perform the following operations

[tex]- 4a + 6a = - 5 + 5 - 18[/tex]
[tex]2a = 0 - 18[/tex]
[tex]2a = - 18[/tex]
[tex]a = \frac{-18}{2} [/tex]
[tex]\boxed{\boxed{a = - 9}}\end{array}}\qquad\quad\checkmark[/tex]

Answer:
[tex]\boxed{\boxed{a = - 9}}\end{array}}\qquad\quad\checkmark[/tex]

Note: Taking the truth (substitute)
[tex]5*(a - 1) - 9*(a - 2) = - 3*(2a + 1) - 2[/tex]
[tex]5*(-9-1) - 9*(-9-2) = - 3*[2*(-9)+1]-2[/tex]
[tex]5*(-10) - 9*(-11) = - 3*[-18+1]-2[/tex]
[tex]- 50 + 99 = - 3*[-17]-2[/tex]
[tex]49 = 51-2[/tex]
[tex]49 = 49\:(TRUE)[/tex]

Therefore: a = - 9